Maternal HIV infection and preterm delivery outcomes at an urban district hospital in KwaZulu-Natal 2011. Issue 1 (4th March 2016) - Naidoo, Mergan; Sartorius, Benn; Tshimanga-Tshikala, Guy
Abstract : Background: The seroprevalence of human immunodeficiency virus (HIV) in pregnant women attending public facilities in KwaZulu-Natal province in 2011 was 37%, the highest in South Africa. An association between the HIV status of the pregnant women and preterm delivery, with associated poorer clinical outcomes, has been reported in many studies. The aim of this study was to explore the relationship between preterm delivery and maternal HIV infections at an urban district hospital in KwaZulu-Natal in 2011. Method: The associations and outcomes of preterm deliveries at a high patient load urban district hospital were determined using a retrospective cohort study. Results: Of the 250 consecutively enrolled patients, 23 women (9%) [95% confidence interval (CI): 5.90–13.50] delivered 25 preterm infants. Ninety-two women (37%) (95% CI: 30.80–43.10) were found to be HIV positive, of whom 13 (14%) (95% CI: 7.70–23.00) delivered preterm neonates, compared to 10 of the 158 women (6%) (95% CI: 3.10–11.30) of the HIV-negative mothers. HIV-positive mothers were significantly more likely (~ 4 fold) to have preterm deliveries than their HIV-negative counterparts, following multivariable adjustment [odds ratio (OR) 4.09, 95% CI: 1.37–12.17] ( p 0.010). Hypertension was the only other risk factor to remain significantly associated with preterm delivery following multivariable adjustment (OR 0.07, 95% CI: 0.02–0.28) ( p < 0.001). Conclusion: The risk of preterm delivery is elevated in HIV-infected pregnant women. HIV-positive pregnant women should be targeted for improved antenatal care and intensive counselling.